Configurable version management hardware transactional memory for embedded multiprocessor field-programmable gate array - Jeevan Sirkunan, 1989- author; Muhammad Nadzir Marsono; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2015